Hemispheric Asymmetries in Radial Line Bisection: Role of Retinotopic and Spatiotopic Factors - Sergio Chieffi; Giovanni Messina; Ines Villano; Antonietta Messina; Ciro Rosario Ilardi; Marcellino Monda; Monica Salerno; Francesco Sessa; Maria Pina Mollica; Gina Cavaliere; Giovanna Trinchese; Fabiano Cimmino; et al. (Frontiers in Psychology, 2018)
Previous studies showed that healthy individuals bisect radial lines oriented along the midsagittal plane farther than the true center (distal bisection bias). It was proposed that the distal bisection bias depended on the presence of an attention bias directed toward far space (distal attention bias) and that this bias is related to the activity of the occipitotemporal visual processing stream. Other studies have also suggested that a similar distal attention bias is linked to the activity of the right hemisphere. In the present experiment we investigated whether distal bisection bias increased when radial lines were placed in the left hemispace. Furthermore, we also examined whether the bisection bias was enhanced by the use of the left hand, as left hand movements are mainly controlled by the right hemisphere. Right-handed participants were asked to bisect radial lines presented below eye level along the midsagittal plane (central lines), or laterally and parallel to the midsagittal plane, in the left or right hemispace (left and right lines, respectively). Participants used their right or left hand. The results showed that participants consistently bisected left and central radial lines farther than (i) the true center and (ii) the subjective midpoint of right radial lines. Conversely, they bisected accurately right radial lines. The hand did not influence bisection error. The present study suggests that the distal bisection bias found in the bisection of left radial lines might depend on the presence of a distal attention bias related to right hemisphere activity. The relative contribution of retinotopic and spatiotopic factors in producing the distal bisection bias is discussed.